Rhizo-Creation of Second-Language Teachers’ Capacity for Technological Integration - Bangou, Francis (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
This article puts to use the work of Deleuze and Guattari to build new knowledge and understanding associated with the circumstantial nature of becoming a technology-capable language teacher through experimentations with/in the agencements of an ongoing research project associated with the design and delivery of a 12-week online graduate course in computer-assisted language learning (CALL). Methodologically, data collection encompassed participants’ assignments, semi-structured interviews, course materials, and researcher’s journal. Moreover, rhizoanalysis was deployed to map change and potentialities in teachers’ becoming. Scholarly contributions to the fields of technology, learning, and teacher education relate to re-theorizing the role and effect of human, expressive, and material elements in teacher education in CALL, as well as developing new methodologies to research micro-level singularities and emergent potentialities for teaching and learning with/in teacher education.